Journalistic treatment of domestic violence during the COVID-19 pandemic in Peru - Aragón Cortez, Sara Alejandra (2022)
The general objective of the study was to know the journalistic treatment of El Comercio and La República on domestic violence during the COVID-19 pandemic in Peru between the months of March 2020 and March 2021.. The method used was content analysis, the design was basic, descriptive, exploratory and quantitative of a non-probabilistic sample from our units of analysis. Population and sample: Throughout the year, the months with the highest number of news articles on domestic violence were May (La Republica with 6 articles) and June (El Comercio with 5 articles).  In order to be able to analyze equal numbers for each newspaper, it was decided to eliminate a note at random from the first media outlet. In this sense, the journalistic coverage of this public health problem in the newspapers El Comercio and La Republica was analyzed based on the agenda setting and framing perspectives to identify the topics and frames that these media have addressed in order to know the treatment they have given to this fact. According to the hypothesis proposed, it was concluded that the press gave importance to the different forms of domestic violence, acquiring its own scheme of coverage and emphasizing frames such as those of human interest and attribution of responsibility.